The lives of two lamas of Naṅ-chen : Gter-ston Mi-ʼgyur-rdo-rje and Tshogs-gñis Padma-dri-med-ʼod-zer - Thugs-kyi-rdo-rje, 17th cent (Kandro, 1973)
Biographies of Yoṅs-dge Gter-ston Mi-'gyur-rdo-rje, b. 1628, and Tshogs-gñis Sprul-sku Padma-dri-med-'od-zer, b. 1828.